Michael O'Halloran - Stratton-Porter, Gene, 1863-1924 (Salt Lake City, UT : Project Gutenberg, 2005)
"Michael O'Halloran" by Gene Stratton-Porter is a novel written in the early 20th century. The story revolves around a young boy, Mickey O'Halloran, who lives a challenging life as a newsboy in a bustling city while taking care of himself and a sickly young girl named Peaches. The narrative highlights themes of resilience, responsibility, and the power of kindness as Mickey demonstrates unwavering determination to create a happy home despite their difficult circumstances. The opening of "Michael O'Halloran" introduces us to the witty and spirited Mickey, who tackles life$1 (Bs challenges with gritty pragmatism. We see him interact with other newsboys and navigate the struggles of earning a living in the city. Mickey$1 (Bs world changes when he finds Peaches, a vulnerable girl in distress, and decides to help her, showcasing his innate compassion and sense of responsibility. As he brings her into his modest home, he begins to face the realities of caregiving$1 (Bbalancing his needs with hers while grappling with his aspirations for a better life for both of them. The opening sets the tone for a touching story that emphasizes the bonds formed through adversity and the impact one person can make in another$1 (Bs life. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Michael_O%27Halloran_(novel)
Release date is 2005-12-01
Produced by Brendan Lane, Richard Prairie and PG Distributed Proofreaders
Keywords: Orphans -- Fiction; Didactic fiction; City and town life -- Fiction; Indiana -- Fiction